If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(v + 4) = 9v + 36 Reorder the terms: -7(4 + v) = 9v + 36 (4 * -7 + v * -7) = 9v + 36 (-28 + -7v) = 9v + 36 Reorder the terms: -28 + -7v = 36 + 9v Solving -28 + -7v = 36 + 9v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-9v' to each side of the equation. -28 + -7v + -9v = 36 + 9v + -9v Combine like terms: -7v + -9v = -16v -28 + -16v = 36 + 9v + -9v Combine like terms: 9v + -9v = 0 -28 + -16v = 36 + 0 -28 + -16v = 36 Add '28' to each side of the equation. -28 + 28 + -16v = 36 + 28 Combine like terms: -28 + 28 = 0 0 + -16v = 36 + 28 -16v = 36 + 28 Combine like terms: 36 + 28 = 64 -16v = 64 Divide each side by '-16'. v = -4 Simplifying v = -4
| 198=6(5x+2) | | -16x^2+24x+1500=0 | | 132=10n+3n-n | | 18=14m-6 | | 18+3x=66 | | x+2y+8z-90=0 | | 6x-5=13+2x | | w/2+17=26 | | 8z-3z=45 | | 14x-4y=-50 | | 1/2(9x+8+9x) | | 180-(10+70)-(60+20)=20 | | (x/-4)=9 | | 7y+3y=50 | | 4v-32=7(v-8) | | 4x-11/2(x^2)-11x+15 | | 8k-19=77 | | 6x-22=+7x+4 | | 2x-7y=1 | | c/-4=-4 | | 4x-11/2x^2-11x+15 | | 9-m/2=13 | | 2x-7y=4 | | 9t=-63 | | -x^2=5 | | tanx=40 | | 6x^4+x^2-1=0 | | y/3-21=-18 | | 5x(x^2-2x+1)=0 | | 6x^2=9x+105 | | 5-2b+5=3b-5-10 | | 3x^2/2=60 |